The grass is greener on the other side: Comparison of green versus brown corporate bonds - Hande Ayaydın Hacıömeroğlu; Seza Danışoğlu; Z. Nuray Güner (Borsa Istanbul Review, 2022)
This study compares the yield-to-maturities on green versus brown corporate bonds on their issue dates, after controlling for the market, firm, bond, and currency characteristics of the bonds. Our analyses show that if these characteristics are not addressed, it is possible to find support for the existence of a “greenium” at a magnitude of about 25 basis points. However, when all yield factors are included in the models, the results change and indicate that issuers do not necessarily enjoy any cost advantage when they issue green bonds, instead of brown bonds. Failure to consider these interactions might lead to biased findings.